The Relationship Between Rainfall and Oil Yield and Fatty Acid Composition of VCO From Coconuts in West Timor - Jasman Jasman; I.G.M. Budiana; Angnes Amtahan; Idalia Norce; Yosep Lawa (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
West Timor is a region of the Republic of Indonesia with a hot and dry climate but has a large coconut plantation and excellent quality coconut oil. This study aims to reveal the correlation between rainfall and coconut oil yield and the fatty acid composition of virgin coconut oil (VCO) produced in the area. The study was conducted by producing VCO from coconuts grown in several areas with varying rainfall in West Timor and then analyzing the fatty acid composition of each VCO product. Furthermore, a correlation analysis was conducted between rainfall data in each sampling area and the fatty acid composition data in the VCO from each area. The results showed no significant correlation between rainfall and coconut oil yield. There was a very strong and negative correlation between rainfall on the one hand and caprylic acid (C8:0) and capric acid (C10:0) content on the other hand. There was a very strong and positive correlation between rainfall on the one hand and lauric acid (C12:0) and myristic (C14:0) content on the other hand. The correlation between rainfall and long chain fatty acids (in this case C16-C18) is low.